Geometric considerations for the 3D printing of components using fused filament fabrication - Aguilar Duque, Julian Israel; García-Alcaraz, Jorge Luis; Hernandez Arellano, Juan Luis (2020)
Demand in 3D printing products using fused filament fabrication (FFF) in industry has been growth a lot with 55% in development of prototypes, 43% in production, and 41% in conceptual models for testing. However, information regarding the manufacturing considerations of geometry-restricted components is still an opportunity area, generating printed components with quality defects. This article is aimed to present some characteristics in geometric components that should be considered during the developing process for components to be produced in FFF to avoid in quality defects. The methodology used considers three stages: first, the reproduction of basic geometric elements and a template that integrates elements with software design; second, the component analysis and the template with software for pre-processing of components, and third, the printing of a template for assumption validation identified in stage two. Findings obtained indicate that the spherical components are geometries with the greatest possibility of defect generation during the FFF printing process. The complexity of the template allowed to identify that the template orientation is a factor that generates defects; for example, with 0° orientation regarding the X axis generates 40,008 risk points for defect and for 30° orientation there are 6658 risk point defects. Therefore, it is advisable to consider avoid geometries associated with sphericity and cylindrical characteristics as possible in the design processes, since these geometries require specific processes to achieve the finishing quality.